Cloud ethics : algorithms and the attributes of ourselves and others - Amoore, Louise (Duke University Press, 2020)
"CLOUD ETHICS focuses on the ethical dimensions and political impact of algorithmic decision-making and cloud computing. Algorithms have become pervasive in supplying solutions for state decision-making and risk management, from border and immigration control, to drone strikes, to the criminal justice system. Acknowledging that algorithms are inherently opaque and illegible, Amoore argues that we can neither encode ethics into the operations of algorithms nor hold algorithms themselves responsible for their actions in the world. Instead, we must exercise this ethical responsibility through our engagement with the conditions under which algorithms emerge. Amoore proposes a "cloud ethics" that can analyze the ethico-politics of the algorithms as they formulate and modify themselves through interactions with data. First, Amoore considers the political character of cloud computing. She contrasts understandings of cloud forms-the identification and spatial location of the data centers where the cloud is thought to materialize, which spark questions like "where is the cloud?"--With cloud analytics, which see the cloud as an analytical gathering of algorithms with data. The machine learning of surgical robotics serves as an example of why algorithms cannot be considered either good or evil: these robots can perform precise surgeries to save lives, but they also potentially endanger lives through error and miscalculation. Responding to public concerns that algorithms can act in a way that is irrational or mad, Amoore argues that algorithms depend more on the act of incorporating data than on the source code itself-and often when algorithms appear to act in a way that's mad, they are exhibiting qualities of their own rationality. Finally, Amoore puts forward her vision of a critical cloud ethics, encouraging scholars to play with the arrangements, thresholds, and assumptions of algorithms to give doubtful accounts of algorithms, which accept potential incoherence instead of holding out for the promise of a particular claim to truth. CLOUD ETHICS will interest scholars in geography, media studies, science and technology studies, history of science and history of computing, and critical theory"--